Current trends and possible solutions for delay in patient discharge: observations from a tertiary care paediatric hospital in Mumbai - Rao, Shirish; Kumar, Ankit; Pandit, Niraj; Jain, Nidhi; Khatri, Karthik; Bodhanwala, Minnie; Venkatesh, Sumitra (International Journal of Contemporary Pediatrics, 2023)
Delay in discharge of the patient reduces bed availability in any healthcare organization. In spite of advancement in medical systems and hospital management, delay in patient discharges still exist. Hence, there was a need to evaluate factors contributing to the delay in an exclusive paediatric hospital. A study of patient discharges from a private and a general ward was undertaken at a tertiary care paediatric hospital in Mumbai, between September-October 2021. A total of 60 discharges, 30 from each ward were analysed. The time from discharge order given by the consultant to that of the patient leaving the hospital and the reasons for delay were recorded by the investigators. The hospital followed a policy of 180 min for a discharge. The mean duration of discharge in the general ward was 153.18±34.60 min and whereas it was 165.41±62.29 min in the private ward. However, 28% discharges in general ward and 43% discharges in private ward were delayed with a mean of 5.23±10.04 and 20.66±26.88 min respectively. Time taken for billing and making of discharge sheet contributed to the maximum delay in both wards. Though the mean discharge time in both wards was found to be within the standards, a significant proportion were still delayed. We suggest a multidisciplinary team consisting of administrators, nurses, resident doctors and consultants to help ease the overall burden on the healthcare system.